Nutritional Interventions for Growth Performance of Dwarf Gourami, Colisa Lalia (Hamilton, 1822) - Upasana Sahoo, B. K. Mahapatra; G. H. Pailan; Paramita B. Sawant; Munilkumar Sukham; Shubendu Datta (Journal of Indian Fisheries Association, 2019)
Growth performances of dwarf gourami, Colisa lalia, by subjecting to diﬀerent nutritional interventions were studied. The study included a comparative analysis of the isonitrogenous and isocaloric formulated feeds with life feed, Tubifex, to get the best formulated feed composition which gives similar results as the live feed. The best result (Length gain 1.03 ± 0.04 cm, Weight gain 1.12 ± 0.02 g, Weight gain 120.75 ± 1.63 %, SGR 0.88 ± 0.01) was observed in the treatment fed with live feed, Tubifex. Similar results, except length gain value, were observed in treatment fed with formulated feed through 4% supplementary feed mix, with no significant diﬀerence (p